RESSOURCES FORESTIÈRES, NOUVEL ENJEU DES CONFLITS EN RÉPUBLIQUE DEMOCRATIQUE DU CONGO ? Regard sur la Réserve de Faune à Okapis - Edocin PONEA TEKPIBELE MASUDI (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The Reserve of Fauna to Okapis (RFO), a protected Area (AP) in Democratic Republic of Congo (DRC) appears like an epicentre of the violence in that country. During last decade, new dynamics constructed around this reserve raised the veil on a line of fracture between actors, revealing the divergence of their interests. From then on, this region became the rotating plate of a criminal economy whose perpetuation seems to contribute to the prosperity of the protagonists that, at the same time, maintain some incestuous alliances in a sort of a" military commercialism". This article examines the dynamism of the conflicts around the RFO and the stakes of their actors. It tempts, otherwise, to clear up the incestuous role of some actors that encourages the prosperity of a criminal economy of which they pull the dividends. This note is, finally, accompanied by the suggestions, in manner of track of solution to allow the state to control efficiently this violence and to sit its authority for a long time around this reserve.